2011
DOI: 10.1007/s12217-011-9259-4
|View full text |Cite
|
Sign up to set email alerts
|

An in Vitro Study on Tissue Repair: Impact of Unloading on Cells Involved in the Remodelling Phase

Abstract: The number of astronauts involved in longlasting missions and extra-vehicular activities is going to increase in the future. Consequently, the chance of injury due to traumatic events or unexpected emergency surgery will also increase and medical evacuation times to earth will be prolonged. Hence, the need to address requirements for surgery and trauma care in non terrestrial environments will be a priority. Tissue repair in weightlessness should therefore be regarded as a major issue not enough studied to dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 38 publications
6
31
0
Order By: Relevance
“…Its decrease, although not statistically significant (p > 0.05), is consistent with the α-SMA decrease and the lower adhesion ability. These results are in agreement with the findings of our previous experiments, in which significant alterations in the distribution of actin filaments and α5β1 integrins were observed (Monici et al 2011). Also, other authors reported on the effects of cytoskeleton disruption in fibroblasts (Bohmer et al 1996) and μginduced downregulation of genes involved in cytoskeleton organization and adhesion (Beck et al 2014).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Its decrease, although not statistically significant (p > 0.05), is consistent with the α-SMA decrease and the lower adhesion ability. These results are in agreement with the findings of our previous experiments, in which significant alterations in the distribution of actin filaments and α5β1 integrins were observed (Monici et al 2011). Also, other authors reported on the effects of cytoskeleton disruption in fibroblasts (Bohmer et al 1996) and μginduced downregulation of genes involved in cytoskeleton organization and adhesion (Beck et al 2014).…”
Section: Discussionsupporting
confidence: 93%
“…Some studies reported that exposure to microgravity may induce skin atrophy (Neutelings et al 2015), delay and impair wound healing (Davidson et al 1999;Delp 2008;Radek et al 2008), and alter processes involved in it, such as inflammation, apoptosis, cell migration, collagen formation, and ECM deposition (Infanger et al 2006;Pietsch et al 2011;Morbidelli et al 2005;Monici et al 2006Monici et al , 2011Chung and Erickson 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the in vitro wound healing models (scratched fibroblast monolayers) exposed to unloading conditions, the ability of fibroblasts to migrate was significantly decreased, as assessed by both scratch and Boyden chamber assays. Previous studies demonstrated an altered production of ECM molecules, such as fibronectin and collagen I, in fibroblasts and endothelial cells cultured in µg simulated by RPM [30]. A relationship could be speculated between inability to migrate and altered ECM production, which could be also a cause of the scarce de novo formation of reparative connective tissue observed in the leeches exposed to µg (Figure 4).…”
Section: Discussionmentioning
confidence: 82%
“…In vitro studies on immune cells, fibroblasts, endothelial, and epithelial cells cultured both in real and modeled µg conditions show alterations of functions involved in wound healing, such as phagocytosis, adhesion/migration, apoptosis, proliferation, intercellular cross-talking, production of inflammatory mediators, ECM molecules, growth factors, and so on [26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%